Elena Ferrante in China - Restucci, Francesca (Annali di Ca’ Foscari: Serie Orientale, 2023)
The international success of the Italian quadrilogy L’amica geniale (My Brilliant Friend) is roaring, the People’s Republic of China (PRC) being no exception to its popularity. The narrative, representative of a specific place and historical period of Italy, is dense with a heavy cultural load. This article aims to describe how Italian culture has been properly introduced into China: the study is conducted through a systematic categorisation of the cultural references retrieved in the first volume and their correspondent translation strategies, triangulated with a semi-structured interview with the translator